Recyclable ZnO/Fe3O4 nanocomposite with piezotronic effect for high performance photocatalysis. (April 2022) - Zhang, Dongmei; Zuo, Xudong; Gao, Wei; Huang, Hui; Zhang, Hao; Cong, Tianze; Yang, Shuaitao; Zhang, Jiandong; Pan, Lujun
Highlights: The ZnO/Fe3 O4 nanocomposites have been synthesized by facile solvothermal method. The piezoelectric potential could be produced and modulated in ZnO/Fe3 O4 . The photocatalytic ability of ZnO/Fe3 O4 could be enhanced by the piezotronic effect. The ZnO/Fe3 O4 nanocomposites reveal excellent recyclability. Abstract: The unrecyclability and low photocatalytic performance are two important problems that significantly limit the usages of ZnO in photocatalysis. In this article, ZnO/Fe3 O4 nanocomposites with residual expansion strain have been synthesized by solvothermal method and sintering-cooling processes. On one hand, the addition of Fe3 O4 nanoparticles provides a possible way for recycling the composites by magnetic attraction. On the other hand, the existence of residual expansion strain in ZnO is favorable for the introduction of piezoelectric potential, which provides an internal driving force for decreasing the recombination rate of photoinduced electron-hole pairs, and improves photocatalytic ability of the ZnO/Fe3 O4 nanocomposites. Compared with the composites with little residual expansion strain, the photocatalytic activity of the composites with large residual expansion strain has been increased by 66%. This research shows the possible applications of piezotronic effect in photocatalysis and related areas, providing a new strategy to prepare recyclable photocatalysts with improved photocatalytic performance. Graphical abstract: Image, graphical abstract